Evaluation of malaria microscopy diagnostic performance at private health facilities in Tanzania - Billy Ngasala; Samweli Bushukatale (Malaria Journal, 2019)
Abstract Background The World Health Organization (WHO) recommends use of parasitological diagnosis of malaria for all age groups in all malaria transmission settings. Many private health facilities rely on malaria microscopy for malaria diagnosis. However, quality of malaria microscopy is affected by number of factors including availability of skilled laboratory microscopists and lack of quality assurance systems in many malaria endemic countries. This study was carried out to assess quality of malaria microscopy in selected private health facilities in Tanzania. Methods A cross sectional study was conducted from August to September, 2017. A total of 40 private health laboratories in five regions were invited to participate in the study. Data were collected by distributing standardized pre-validated malaria slide-panels to each health facility. Sensitivity, specificity, and strength of agreement (with kappa score) were calculated to assess performance in detecting and quantification of Plasmodium species. Results Among the 40 health facilities, 31 (77.5%) returned their results to the reference centre (Muhimbili University of Health and Allied Sciences). Overall, the measures of malaria diagnostic accuracy were high, i.e. the sensitivity and specificity of malaria parasite detection by microscopy in the health facilities were 84.3% (95% CI 77–90) and 90.8% (95% CI 83.3–95.7), respectively. There was substantial agreement in parasite detection with (Kappa value: 0.74 (95% 0.65–0.83). However, only 17.8% (24 of 134) of blood slides were interpreted correctly at the health facilities in terms of parasite density counts. Conclusion Although there was substantial agreement between the private health microscopists and experienced microscopists in malaria parasite detection, there was poor performance in parasite counts. This calls for regular in-service training and external quality assessments at private health facilities to enhance the skills of private health facility microscopists in malaria microscopy.